The Effect of Work Stress and Work Environment on Employee Performance at the Trade Apparatus Education and Training Center (Pusdiklat) in Depok - Fitri, Nurul (Pascasarjana Universitas Pasundan, 2025)
This study aims to analyze the effect of work stress (X1) and work environment (X2) on employee performance (Y) both partially and simultaneously. The study used a quantitative method with a sample of 60 employees and various statistical tests, including validity, reliability, classical assumptions, regression, and hypothesis tests. The results of the analysis produced a regression equation Y = 31.641 + 0.191X1 + 0.289X2. The results of the t-test showed that work stress (X1) had a negative and significant effect on employee performance, with a t-count of 1.909> t-table 1.672 and a significance value of 0.000 <0.05. Meanwhile, the work environment (X2) had a positive and significant effect on employee performance, with a t-count of 1.913> t-table 1.672 and a significance value of 0.000 <0.05. Simultaneously, the results of the F test show that work stress and work environment have a significant effect on employee performance (F-count 4.907 > F-table 3.159, significance 0.000 < 0.05). Thus, it can be concluded that a good work environment can improve employee performance, while high work stress can decrease it at the Trade Apparatus Education and Training Center (Pusdiklat) of Depok City